Shallow sampling by multi-shot laser ablation and its application within U-Pb zircon geochronology - Crowley, Quentin; Corbett, Eoghan P.; Simonetti, Antonio; Shaw, Phil; Corcoran, Loretta; Hoare, Brendan C. (My University, 2020)
The interaction of incident laser radiation and sample substrate is complex and difficult to predict. Natural zircons are often both structurally and chemically heterogeneous in 3-dimensional space. Encountering growth-related, structural micro-heterogeneities, inclusions and chemical complexities is almost inevitable during a static ablation of several tens of seconds. A multi-shot approach to laser ablation described here implements a minimal sample exposure time to incident laser radiation by applying multiple 1 Hz shots to a single sample location in delayed succession. This process can be conceptualised as a “slowing down” of a high-frequency (5–20 Hz) static laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) analysis until each laser pulse is distinct albeit transient. The ability to integrate and collate signal pulses for a small number of consecutive laser shots, as opposed to continuously pulsing the laser, produces precise age determinations (~1% reproducibility, 2σ level) on small sample volumes (698 ± 22 μm3 on 91500 zircon standard). The multi-shot LA-ICP-MS protocol employed here significantly reduces the effect of ‘downhole’ fractionation as the resultant craters are extremely shallow (as shallow as 0.56 ± 0.02 μm on 91500 zircon standard) and maintain an aspect ratio of ≪1. Further benefits include a reduced probability of thermally induced effects (e.g., substrate melting), plasma loading, and the potential for signal mixing (with depth) in a heterogeneous sample.
PUBLISHED
Keywords: Low sample volum; Multi-shot LA-ICP-MS; Sub-micron sampling; Depth resolution; Downhole fractionation; LIEF; Nanoscience & Materials; Smart & Sustainable Planet; Mass Spectrometry; U-PB GEOCHRONOLOGY; ZIRCONS